[Stream Through Glacial Valley] - Streng, Evelyn Fiedler (1975)
Photograph of a stream crossing a glacial valley. The water winds through the green fields in the foreground and connecting to a larger river in the background. Mountains surround the valley where several white buildings with red roofs sit on farmland. Grey clouds hang in the white sky at the top of the photograph.